Direct utilization of CO2 via methanol synthesis for natural gas fields with high CO2 concentration - Kim, Seungwoo; Kim, Yoori; Oh, Se Young; Park, Myung June; Lee, Won Bo (Journal of Natural Gas Science and Engineering, 2021)
CO2-rich natural gas fields are left abandoned because of the large amount of energy required for the complete separation of CO2 and the relatively low CH4 content. To utilize such natural gas, this study investigated the direct transformation of CO2 via reforming and methanol synthesis. An acid gas removal unit was used to remove H2S and release sweet gas, including a mixture of CO2 and CH4. Two different amine absorbents were considered to compare the effects of CO2 concentration in the sweet gas—methyldiethanolamine (MDEA) and a mixture of MDEA and diethanolamine (DEA). Sweet gas was fed into the reforming process, where syngas was produced via dry reforming. Because dry reforming produced syngas with a small amount of H2, steam supplementation through a high-pressure steam generator was considered to promote steam reforming by recycling the water produced by the reverse water-gas-shift reaction or by feeding additional water. Syngas was fed into the methanol synthesis process, and the recycled cases showed higher methanol production rates than the open-loop cases despite the decreased local conversion of CO. Techno-economic analysis was performed to determine the optimal configuration to maximize profitability; the Case II-5-R (a mixture of MDEA and diethanolamine (DEA), steam supplementation of 1500 kgmole/h, recycle loop) was selected as the optimal case with a payback period of 4.24 years and return on investment of 0.173 y−1. The techno-economic analysis proved that the proposed strategy can promote further development of natural gas fields with high CO2 concentrations.
Keywords: CH 4; CO 2 concentration; CO2 utilization; CO2-rich natural gas field; Methanol synthesis; Methyldiethanolamine; Mixed reforming; Sweet gas; Syn gas; Techno-Economic analysis; CO2 utilization; CO2-Rich natural gas field; Methanol synthesis; Mixed reforming; Techno-economic analysis